Implementation of the Independent Learning Curriculum and Deep Learning Approach in Educational Institutions - Syamsi, Syamsi; Junaidi, Rahmat; Hidayat, Burhanuddin; Syofyandi, Rozi; Lahmi, Lahmi (Ahlussunnah: Journal of Islamic Education, 2025)
The implementation of the curriculum at the primary and secondary education levels, namely Elementary School, Junior High School, and Senior High School, has undergone significant transformation through the application of the Freedom of Learning program and the Deep Learning approach. The Freedom of Learning program encourages flexibility in learning, teacher creativity, and student independence in the learning process, while the Deep Learning approach emphasizes in-depth mastery of concepts, critical thinking skills, and the ability to solve complex problems. This study aims to analyze the implementation of the curriculum at various levels of education and evaluate the effectiveness of applying both approaches in improving the quality of learning. The research method used in this study is qualitative descriptive research. Qualitative descriptive is a research procedure that produces descriptive data in the form of written or spoken words about people and observable behaviors to discover truths that are acceptable to human reason. The data collection technique used is a literature study, where data is obtained from books and previous research journals relevant to the topic being discussed. The results of the study show that the implementation of Freedom of Learning provides space for innovation in teaching methods and increases student motivation to learn, while the Deep Learning approach is able to improve students' overall understanding of concepts as well as their analytical and synthesis skills. These findings emphasize the importance of integrating both approaches to create relevant, adaptive, and quality learning in the modern era of education.